Phytochemical, antioxidant, antimicrobial and antiproliferative potential of Elaeagnus indica. (July 2019) - Srinivasan, R.; Aruna, A.; Manigandan, K.; Pugazhendhi, A.; Kim, Myunghee; Shivakumar, M.S.; Natarajan, D.
Abstract: The present investigation was aimed to evaluate the phytochemical nature as well as antimicrobial, antioxidant and antiproliferative properties of Eleaegnus indica . Different solvent (hexane, chloroform, acetone, ethyl acetate, and methanol) leaf extracts of E . indica were tested for their antimicrobial, antioxidant, antiproliferative and phytochemical properties by adopting standard methods. The extracts of E . indica were found to be good sources of a variety of phytoconstituents i . e ., phenols (72.97 μg/mg GAE), flavonoids (92.07 μg/mg CE), tannins (62.97 μg/mg TAE), ascorbic acid (154.07 μg/mg AAE), proteins (115.46 μg/mg BSAE) and carbohydrates (193.77 GE). The acetone extract exhibited strong in vitro antioxidant potentials (NO ● IC50  = 39.43 μg/mL, ● OH IC50  = 43.91 μg/mL, O2 ●- IC50  = 48.30 μg/mL, DPPH ● IC50  = 70.32 μg/mL, and FRAP EC50  = 48.69 μg/mL and total antioxidants 425.92 μg/mg AAE of dry extract) in all the tested methods. All the extracts of E . indica expressed a wide range of antimicrobial potential (6–24 mm) against most of the pathogens used in this study. The methanol extract exhibited remarkably high antibacterial potential against S . epidermidis (24 mm) followed by S . pneumoniae (20 mm) in the well diffusion method. The results of the antiproliferative activity of acetone extract showed a concentration dependent activity on the tested cell lines (U-937 cell line IC50  = 46.75 μg/mL and HL-60 cell line IC50  = 59.46 μg/mL). The present investigation highlighted that the acetone extract exhibited significant antiproliferative, antimicrobial, and antioxidant capacities and has provided scientific evidence for the development of novel antimicrobial, antioxidant and antiproliferative agents from E . indica .